2022
DOI: 10.1097/htr.0000000000000785
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Traumatic Brain Injury and Increased Risk of Stroke: A Systematic Review and Meta-analysis

Abstract: Objective: To determine whether exposure to traumatic brain injury (TBI) is associated with increased risk of stroke in adults compared with referents not exposed to TBI, and to understand whether an association exists throughout the spectrum of injury severity, whether it differs between the acute and chronic phases after TBI, and whether the association is greater with hemorrhagic compared with ischemic stroke after TBI. Setting: A database search was conducted on January 22, 2021. Searches were run in MEDLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
3
7
0
Order By: Relevance
“…On the one hand, previous TBI increased the risk of stroke and its major subtypes in the population in this study (see Supplementary Table 1 ). Similar to our findings in this study, previous case-control or cohort studies from hospital or insurance data also confirmed that previous TBI, even a concussion, increased the odds ratio or incidence of stroke and its subtype [ 6 , 7 , 9 , 12 17 ] and was more closely related to haemorrhagic stroke, including intracerebral haemorrhage and subarachnoid haemorrhage. [ 6 , 7 , 9 , 16 , 17 ] On the other hand, previous stroke also increased the risk of nonconcussion TBI in the population in this survey (see Supplementary Table 2 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…On the one hand, previous TBI increased the risk of stroke and its major subtypes in the population in this study (see Supplementary Table 1 ). Similar to our findings in this study, previous case-control or cohort studies from hospital or insurance data also confirmed that previous TBI, even a concussion, increased the odds ratio or incidence of stroke and its subtype [ 6 , 7 , 9 , 12 17 ] and was more closely related to haemorrhagic stroke, including intracerebral haemorrhage and subarachnoid haemorrhage. [ 6 , 7 , 9 , 16 , 17 ] On the other hand, previous stroke also increased the risk of nonconcussion TBI in the population in this survey (see Supplementary Table 2 ).…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our findings in this study, previous case-control or cohort studies from hospital or insurance data also confirmed that previous TBI, even a concussion, increased the odds ratio or incidence of stroke and its subtype [ 6 , 7 , 9 , 12 17 ] and was more closely related to haemorrhagic stroke, including intracerebral haemorrhage and subarachnoid haemorrhage. [ 6 , 7 , 9 , 16 , 17 ] On the other hand, previous stroke also increased the risk of nonconcussion TBI in the population in this survey (see Supplementary Table 2 ). Regrettably, despite the higher estimated incidence rates of falls and fall-related injuries of 88.0 and 2.8 per 100 person-years in stroke patients, respectively [ 18 ], there is little evidence that stroke increases the risk of TBI.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In an Ohio based study, 1 in 5 adults reported a TBI with loss of consciousness and for 10% of respondents the TBI occurred before they were 15 years old ( Corrigan et al, 2018 ). TBI are associated with long-term health issues including increased risk of stroke ( Esterov et al, 2023 ), early onset dementia ( Bellomo et al, 2022 ), depression ( Lambert et al, 2022 ), and decreased olfaction ( Tai et al, 2022 ). Post-TBI sequelae frequently include fatigue and altered cognition that compromise quality of life and productivity as described by the brain injury associated fatigue and altered cognition syndrome (BIAFAC) ( Yuen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%